Scientific bases for the preparation of heterogeneous catalysts : proceedings of the 10th International Symposium, Louvain-la-Neuve, Belgium, July 11-15, 2010 - Gaigneaux, E. (Studies in surface science and catalysis, 2010)
These meetings, held every four years, bring together researchers from academia and industry and offer a forum for discussions on the chemistry involved in the preparation of industrial heterogeneous catalysts. Contributions focus on the aspects of catalyst preparation. Reports on physico-chemical characteristics of catalysts and catalytic performances are limited to correlations with the preparation parameters. Contains a collection of the papers presented at the workshop.